2013
DOI: 10.1021/jp4071955
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in the Isotropic Phase of Nematogens Using 2D IR Vibrational Echo Measurements on Natural-Abundance 13CN and Extended Lifetime Probes

Abstract: The long time scale orientational relaxation of nematogens in the isotropic phase is associated with the randomization of pseudonematic domains, which have a correlation length that grows as the isotropic-to-nematic phase transition temperature is approached from above. Here we begin to address the fast dynamics of the nematogen molecules within the domains using two-dimensional infrared (2D IR) vibrational echo experiments. The problems of performing ultrafast IR experiments in pure liquids are discussed, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(79 citation statements)
references
References 95 publications
3
76
0
Order By: Relevance
“…We have previously shown that temperature dependent ultrafast two dimensional infrared (2D IR) vibrational echoes and polarization selective pump-probe experiments combined with the findings from OHD-OKE experiments provide an expanded picture of nematogen dynamics in the isotropic phase. 19,20 The 2D IR experiments yield information on the dynamics experienced by non-perturbative probe molecules within a pseudonematic domain, while the complete reorientation dynamics over a very wide range of time scales are reported by the complementary OHD-OKE experiments.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that temperature dependent ultrafast two dimensional infrared (2D IR) vibrational echoes and polarization selective pump-probe experiments combined with the findings from OHD-OKE experiments provide an expanded picture of nematogen dynamics in the isotropic phase. 19,20 The 2D IR experiments yield information on the dynamics experienced by non-perturbative probe molecules within a pseudonematic domain, while the complete reorientation dynamics over a very wide range of time scales are reported by the complementary OHD-OKE experiments.…”
Section: Introductionmentioning
confidence: 99%
“…19,22 Nitrile stretches have previously been shown to be useful vibrational probes for 2D IR experiments, although their utility is frequently limited by the short CN vibrational lifetime. [23][24][25][26] 2D IR spectroscopy provides information on structural dynamics through the measurement of spectral diffusion of a vibrational oscillator, like the CN stretch.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…64,65 In the isotropic phase, the liquid has nematic order (pseudonematic domains) over a correlation length that increases as the I−N transition is approached. 66 Detailed analysis using mode coupling theory of the results of the 2D IR experiments and optical heterodyne detected optical Kerr effect experiments showed that orientational relaxation of the nematogens was far too slow to be responsible for the CN stretch spectral diffusion.…”
Section: Resultsmentioning
confidence: 99%